Targeting Angiogenesis in Breast Cancer: Current Evidence and Future Perspectives of Novel Anti-Angiogenic Approaches - Ayoub, Nehad M.; Jaradat, Sara K.; Al-Shami, Kamal M.; Alkhalifa, Amer E. (Frontiers in Pharmacology, 2022)
Angiogenesis is a vital process for the growth and dissemination of solid cancers. Numerous molecular pathways are known to drive angiogenic switch in cancer cells promoting the growth of new blood vessels and increased incidence of distant metastasis. Several angiogenesis inhibitors are clinically available for the treatment of different types of advanced solid cancers. These inhibitors mostly belong to monoclonal antibodies or small-molecule tyrosine kinase inhibitors targeting the classical vascular endothelial growth factor (VEGF) and its receptors. Nevertheless, breast cancer is one example of solid tumors that had constantly failed to respond to angiogenesis inhibitors in terms of improved survival outcomes of patients. Accordingly, it is of paramount importance to assess the molecular mechanisms driving angiogenic signaling in breast cancer to explore suitable drug targets that can be further investigated in preclinical and clinical settings. This review summarizes the current evidence for the effect of clinically available anti-angiogenic drugs in breast cancer treatment. Further, major mechanisms associated with intrinsic or acquired resistance to anti-VEGF therapy are discussed. The review also describes evidence from preclinical and clinical studies on targeting novel non-VEGF angiogenic pathways in breast cancer and several approaches to the normalization of tumor vasculature by targeting pericytes, utilization of microRNAs and extracellular tumor-associate vesicles, using immunotherapeutic drugs, and nanotechnology.